MONOMYTH: THE HERO’S STRUGGLE OF EZIO AUDITORE IN OLIVER BOWDEN’S ASSASSIN’S CREED RENAISSANCE NOVEL - Noor, Muhammad Akmal Farhan (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
Monomyth as known as hero’s journey was created to define the patterns of stages to become heroes. Every part of the stages consists challenges that force hero struggling to complete the stages. The form of struggle itself is variety depends on the condition and situation based on hero’s background. This research intended to find the hero’s struggle and hero’s journey that appeared in Ezio’s heroic journey. In this research, the researcher analyzed one of the characters from Assassin’s Creed Renaissance novel. In specific, a character, named Ezio Auditore, was analyzed through hero’s journey theory. The data were analyzed with hero’s struggle theory by George R. Goethals and Scott T. Allison, and hero’s journey theory by Joseph Campbel. The data were generated from the actions, dialogues, and other’s character’s narrations as well as Ezio’s struggle through his journey to become a hero. In conclusion, the research revealed that Ezio experienced all three struggles that mentioned by Goethals and Allison, those are pain and hardship, vulnerability and weakness, and evil encounter. It also matched eleven stages from seventeen stages of hero’s journey by Joseph Campbell, those are the call to adventure, refusal of the call, supernatural aid, the crossing of the first threshold, the road of trials, the meeting with the goddess, woman as the temptress, atonement with the father, apotheosis, the ultimate boon, and the crossing of the return threshold. Finally, the conclusion can be drawn is that the findings above strengthen the fact that Ezio Auditore in Assassin’s Creed Renaissance is a heroic story.